Exhaust emissions from heavy-duty vehicles. (20th February 2004) - Barlow, Tim; McCrae, Ian
Exhaust emission tests were conducted on 20 heavy-duty vehicles. These test vehicles were Euro 1 and Euro 2 compliant and included coaches, and trucks ranging from 7.5 to 38 tonne vehicles. The vehicles were tested over the European 13-mode and the FIGE engine dynamometer tests, with some of the vehicles repeat tested using an ultra low sulphur diesel fuel (ULSD). A single test vehicle was tested over a selection of real world driving cycles. In general, Euro 2 vehicles demonstrated lower emissions than Euro 1 vehicles. The ULSD produced large decreases in the emissions of CO and PM with a smaller decrease in NOx . Although Euro 2 vehicles produced less mass of particulate, the number of particles emitted significantly increased when compared to Euro 1. The FIGE and the Truck cycles produced the lowest and similar emission rates, while the bus cycle produced much higher levels, reflecting the importance of vehicle operation on emissions.